"Do as I say, not as I do" - a systematic literature review on the attitude-behaviour gap towards sustainable consumption of Generation Y. (December 2018) - Bernardes, J P; Ferreira, F; Marques, A D; Nogueira, M
Abstract: This paper contributes to a consolidation of the field by narrowing down the gap between sustainable consumption "attitudes/intentions" and actual consumption "behaviour". The adopted methodology is based on a systematic literature review with an initial sample of more than 1000 publications, this paper considers the following inclusion and exclusion criteria throughout the review: research scope, conceptualisation of the terms (e.g. "Sustainable consumption"; "Ethical consumption"; "Green consumption"; "Green consumerism"; "Responsible consumption"), research design (e.g. quantitative, qualitative experimental studies), segments of consumers (Generation Y) and time frame. A qualitative research approach will be adopted in this paper, to safeguard the inclusion of methodologically diverse studies. Additionally, because the mentioned concepts have evolved over time and raised so many different interpretations, a qualitative approach is considered more pertinent. The focus of the review is to build up coherence regarding the sustainable consumption attitude-behavior gap. The paper concludes with a discussion of challenges and recommendations for future work in the field, namely, the need to encourage and educate consumers to live a more sustainable lifestyle and to design and implement responsible marketing tools to communicate the value of sustainable consumption.